MODERNIZATION OF HIGHER PROFESSIONAL EDUCATION IN MODERN CONDITIONS - Korotkova Tatyana Sergeevna,; Narynbaeva Aina Serikovna,; Dosmanbetova Aliya Serikbaevna,; Zhumaxanova Karlygash Muratovna, (Academic Journal of Physical and Chemical Sciences, 2020)
The goal of the work is to study the direction of development and modernization of the higher education system in Kazakhstan. In the course of work, analysis and synthesis, a comparison method and a factor method were used, with the help of which the world experience in creating an education system is shown. In modern conditions, quality education enhances the competitiveness of not only specialists, but also the country's economy as a whole. The competitiveness of vocational education provides an opportunity for the further development of science and technology, increasing employment and improving the welfare of society. The results of the work are recommendations for the development of an effective education system. The scope of the research results is in the legislative activity of the state and the functioning of higher education institutions. The results of the analysis of the world and Kazakhstani experience in the development of the education system make it possible to evaluate the effectiveness of the current model of education. Modernization of higher education and science should become a priority in the development of state programs. However, during the reorganization, emphasis should be placed on improving the quality indicators of universities, rather than quantitative parameters.